Oxidative stress induced nephrotoxicity in chronic low dose organophosphates (OP) exposure - Aung, Sanda; Abdullah, Nor Zamzila; A.Talib, Norlelawati; Mat Zainone, Zamzuria; Abdul Razak, Tariq (Malaysian Society of Pathologists, 2018)
Introduction: There were significant epidemiological evidences that suggested the association of end-stage renal diseases of unknown aetiology with chronic pesticide exposure.Our previous assessment of renal tissues from Sprague-Dawley rats exposed to chronic low dose OP had found significant microscopic features consistent with renal tubular damage. This study postulated that the renal damage is the consequences of oxidative stress which may lead to cell death through apoptosis. The aims of the current study is to determine the pathways involved in the above microscopic changes. Materials & Methods: Two groups of males Sprague-Dawley rats of 6 rats each: control group and exposed group (received an alternate day of subcutaneous 18.0 mg/kg BW chlorpyrifos) were sacrificed at 150 days. A small tissue section from the renal cortex was preserved in RNAlater whilst the other half of the renal was preserved in formalin for tissue processing. RNA was purified from the tissue preserved in RNAlater and subsequently subjected to qPCR array on real-time platform. The relative expression of selected markers representing the oxidative stress and apoptosis pathways was normalized to two reference genes and quantitatively measured using ΔΔCq method. Immunohistochemistry for MDA and p53 were performed in formalin fixed paraffin embedded renal tissue. Results: There were significant downregulation of GR (p=0.04), NOS2 (p=0.03) and Ripk3 (p=0.01) and significant upregulation of p53 (p=0.02). Subsequently IHC test showed significant MDA and p53 expression. Discussion: The OP exposure to the kidney results in tubular injury through oxidative pathways and subsequent cell arrest by activation of p53.